IMPLEMENTASI PROGRAM BADAN USAHA MILIK DESA (BUMDes) DI DESA DARMASARI KECAMATAN BAYAH KABUPATEN LEBAK (STUDI KASUS : PROGRAM JASA ANGKUT SAMPAH DAN DAUR ULANG SAMPAH) - yonadikadiantoro24; Yeni Widyastuti (LPPM STIA Banten, 2024)
Village-Owned Enterprises (BUMDes) are an important instrument in rural economic development which focuses on managing the local potential of villages. BUMDes was formed with the aim of providing necessary services for productive businesses, especially for village communities who are classified as poor. This research aims to find out how the Village-Owned Enterprises (BUMDes) Program is implemented in Darmasari Village, Bayah District, Lebak Regency. This research uses a descriptive method with a qualitative approach. Qualitative-descriptive research aims to describe the implementation process, provide symptoms, facts or events systematically and accurately and in detail and in depth regarding the Implementation of the Village-Owned Enterprise Program (BUMDes). The research results in the implementation of BUMDes are viewed from the dimensions of size and policy objectives, resource dimensions, characteristics of implementing agents, attitudes/dispositions of implementers, dimensions of the economic, social and political environment. It is hoped that the final conclusion of this research will be the development of a more effective and sustainable BUMDes model in strengthening the village economy, especially in Darmasari Village, Bayah District, Lebak Regency. Keywords: BUMDes, village economy, community empowerment, economic independence, community welfare